2019
DOI: 10.3390/ani9030085
|View full text |Cite
|
Sign up to set email alerts
|

Growing Pigs’ Interest in Enrichment Objects with Different Characteristics and Cleanliness

Abstract: Enrichment objects can be a practical way to provide rooting and chewing material to growing pigs, on which they can express species-specific behaviors. The challenge is to provide enrichment objects that will satisfy pigs’ behavioral needs, while being practical and low-cost for the producers. Two trials were conducted to evaluate the effects of object characteristics such as design, location, cleanliness or degree of wear, on pigs’ interest over time. The first trial compared seven objects, varying in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
(52 reference statements)
1
19
0
Order By: Relevance
“…Recent studies confirm lower interaction with logs presented on the floor, versus a hanging log, possibly caused by soiling with faeces [87]. However, the study on this issue by [96] found that cleaning (plastic and rubber) objects did not affect the pigs’ interaction with them.…”
Section: Pig Enrichment In Global Practicementioning
confidence: 99%
“…Recent studies confirm lower interaction with logs presented on the floor, versus a hanging log, possibly caused by soiling with faeces [87]. However, the study on this issue by [96] found that cleaning (plastic and rubber) objects did not affect the pigs’ interaction with them.…”
Section: Pig Enrichment In Global Practicementioning
confidence: 99%
“…Furthermore, the presentation of the enrichment contributes to the observed differences in usage. Although wooden objects in general did not occupy pigs for a high percentage of their time, a wood block elevated from the floor on one side by a plastic ring that could be moved through the pen was in use by at least one pig for 65% of the time (13.5 pigs/pen), indicating that this may be a more suitable way of providing wood than suspending it or mounting it to the wall [78]. In the same study, a set of spring-mounted plastic balls attached to the floor in a close triangular pattern were also occupied frequently (33% of the time by at least 1 pig).…”
Section: Time Spent In Interaction With Non-straw Enrichmentmentioning
confidence: 99%
“…Furthermore, a reduction in the manipulation of floor-based enrichments due to soiling is a concern [67]. However, the aforementioned high use of the spring-mounted balls and the woodblock with ring, and an absence of an effect of regular cleaning of such devices [78] indicates that soiling is not necessarily a problem for all floor-based devices. Lastly, any enrichment that is inaccessible to the pig, e.g., items suspended too high or biting substrates that are too large for the pig to fit its mouth around, will obviously not be effective [5].…”
Section: Time Spent In Interaction With Non-straw Enrichmentmentioning
confidence: 99%
See 2 more Smart Citations